2006
DOI: 10.1002/chir.20287
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acidic and basic additives on the enantioseparation of basic drugs using polysaccharide‐based chiral stationary phases

Abstract: The enantioseparation of nine commercially available basic drugs was achieved on polysaccharide-based chiral stationary phases with the acidic additive ethanesulfonic acid and the basic additive butylamine. Seven different commercially available CSPs were used for the study (AD, AS, OD, OJ, OG, OB, and OC). Mobile phase additives have been proven to be essential in obtaining satisfactory enantio-resolution in terms of both efficiency and selectivity. Significantly improved selectivities were obtained for the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…Now, a chiral separation can be achieved on many different CSPs based on different chiral recognition mechanisms or in different separation modes on the same CSP. For example, the β-adrenergic blockers, an important class of chiral amino alcohol drugs, were directly resolved on a wide array of CSPs, including phases based on tris(3,5-dimethylphenylcarbamate) cellulose in normalphase (NP) mode [70,142,143] and reversed-phase (RP) mode [70], macrocyclic glycopeptides in polar organic mode (POM) [53][54][55] and SFC [144], proteins in RP [145], β-cyclodextrins in RP [69] and POM [73], chiral crown ethers in POM [134], and Pirkle-type chiral selectors in NP [146].…”
Section: Chiral Methods Development In the Pharmaceutical Industrymentioning
confidence: 99%
“…Now, a chiral separation can be achieved on many different CSPs based on different chiral recognition mechanisms or in different separation modes on the same CSP. For example, the β-adrenergic blockers, an important class of chiral amino alcohol drugs, were directly resolved on a wide array of CSPs, including phases based on tris(3,5-dimethylphenylcarbamate) cellulose in normalphase (NP) mode [70,142,143] and reversed-phase (RP) mode [70], macrocyclic glycopeptides in polar organic mode (POM) [53][54][55] and SFC [144], proteins in RP [145], β-cyclodextrins in RP [69] and POM [73], chiral crown ethers in POM [134], and Pirkle-type chiral selectors in NP [146].…”
Section: Chiral Methods Development In the Pharmaceutical Industrymentioning
confidence: 99%
“…Similar to identifying parameters for successful enantiomeric separation by HPLC, [231][232][233][234] screening CSPs, alcohol cosolvents, and acidic and basic modifiers are integral components in developing successful chiral separations by SFC. [256][257][258] A note of caution is appropriate as reversal of elution order of enantiomers is neither uncommon nor currently predictive in HPLC and SFC separations. [259][260][261][262] Therefore, spectroscopic characterization of the eluted enantiomers is paramount to successfully correlating configuration with eutomer (biologically active enantiomer) and distomer (biologically inactive enantiomer).…”
Section: Current Toolbox-chiral Separationsmentioning
confidence: 99%
“…It has been demonstrated that these compounds are essential for the separation of acidic and basic drugs [54,55]. Trifluoroacetic acid is a frequently used acid.…”
Section: Normal-phase Liquid Chromatographymentioning
confidence: 99%
“…Acetic acid and alkylsulfonic acids, such as ethanesulfonic acid, can also be dissolved in the mobile phase. Triethylamine and diethylamine are the common basic additives, while butylamine and dimethylethylamine are possible alternatives [45,55]. The influence of these additives, generally used in concentrations of 0.1% (v/v) in the mobile phase, is versatile.…”
Section: Normal-phase Liquid Chromatographymentioning
confidence: 99%